INTERNALISASI NILAI KREATIVITAS MELALUI PENGEMBANGAN BUKU RAMAH CERNA KATEGORI PEMBACA B2 DI SEKOLAH DASAR - Prasetyo, Yoga; Aryanto, Sani (LPPM Universitas Bina Bangsa, 2024)
Literacy is a basic ability that children need to have from an early age. The ability in question is in the form of reading and writing, this literacy is not only used in school learning but can also be a provision for children to be able to use in their daily lives, because literacy must be the basis of early childhood habits. Literacy is one of the focuses of the Indonesian government, because it is believed to be a solution to improve thinking skills through reading and writing activities. Digest-friendly books are believed to be a solution in strengthening early literacy in elementary school. Therefore, the aim of this research is to internalize the value of creativity through the development of digest-friendly books for the b2 reader category in elementary schools. This research uses a Research and Development (R&D) research design through the ADDIE development model, including five steps, namely Analysis Design, Development, Implementation, and Evaluation involving 1 teacher and 30 students in class 1 of Margahayu XVIII Elementary School, Bekasi City. The rationalization of school selection is based on based on recommendations from several schools in Bekasi City to conduct thesis research, because this shows that literacy skills need to be improved. However, the results of this research are considered successful in developing a digest-friendly book that makes it easier for teachers in the process of teaching early literacy and is considered very good with a percentage of 82%. This research produced a book title that is considered to have internalized creative value Profil Pelajar Pancasila.